Different categories of VO2 kinetics in the `extreme` exercise intensity domain - Ozkaya, O.; Jones, A. M.; Burnley, M.; As, H.; Balci, G. A. (Journal of Sports Sciences, 2023)
The aim of this study was to classify potential sub-zones within the extreme exercise domain. Eight well-trained male cyclists participated in this study. The upper boundary of the severe exercise domain (Pupper-bound) was estimated by constant-work-rate tests. Then three further extreme-work-rate tests were performed in discrete regions within the extreme domain: extreme-1) at a work-rate greater than the Pupper-bound providing an 80-110-s time to task failure; extreme-2) a 30-s maximal sprint; and extreme-3) a 4-s maximal sprint. Different functions were used to describe the behaviour of the VO2 kinetics over time. VO2 on-kinetics during extreme-1 exercise was best described by a single-exponential model (R2 = 0.97; SEE = 0.10; p < 0.001), and recovery VO2 decreased immediately after the termination of exercise. In contrast, VO2 on-kinetics during extreme-2 exercise was best fitted by a linear function (R2 = 0.96; SEE = 0.16; p < 0.001), and VO2 responses continued to increase during the first 10-20 s of recovery. During the extreme-3 exercise, VO2 could not be modelled due to inadequate data, and there was an M-shape recovery VO2 response with an exponential decay at the end. The VO2 response to exercise across the extreme exercise domain has distinct features and must therefore be characterised with different fitting strategies in order to describe the responses accurately.